CT-Scan Findings of Patients Presented with Hepatic Mass attended at Tertiary Care Hospital in Bangladesh (Journal of Current and Advance Medical Research, 2015)
Background: CT-scan findings give a well delineated impression on hepatic mass. Objective: The purpose of the present study was to observe the CT-scan findings of hepatic mass. Methodology: This cross sectional study was carried out in the department of Radiology and Imaging MMC in collaboration with the same department of BSMMU, DMC, Dhaka during the period of 1st January 2006 to 31st December 2007 to establish the usefulness of CT scan in the diagnosis of hepatic mass and its validity by determining sensitivity, specificity, PV, NPV, and accuracy. A total of 50 patients were admitted in the Department of Medicine and Department of Hepatobiliary of MMCH, BSMMU, and DMCH with the clinical diagnosis of fever, abdominal pain, anorexia, nausea/vomiting, loss of appetite, jaundice, weight loss and ascites. They were sent to the department of Radiology and Imaging and of respected hospitals for CT evaluation, confirmation and to see the extension for planning of proper management. Result: A total number of 50 hepatic mass patients were recruited in this study. CT findings of all patients showed 29 had lesions on right lobe, six patients had on left lobe and 15 patients had lesion on both lobe (p value